Squamous cell carcinoma arising in mature cystic teratoma of ovary - Patni, Ranu (J Midlife Health, 2014)
Squamous cell carcinoma of the ovary is a rare condition and usually arises in mature cystic teratoma (MCT) or dermoid cyst of the ovary. The reported incidence of malignant transformation in MCT is approximately 2%. A case of squamous cell carcinoma arising in a dermoid cyst of the ovary presenting at an early stage is presented here. A 53-year-old postmenopausal lady, presented with the complaint of pain in right lower abdomen since one month and a large complex abdomino-pelvic mass on examination and investigations. Final histopathology was reported as squamous cell carcinoma of left ovary arising from dermoid cyst and a benign dermoid cyst in the right ovary. The patient was assigned to squamous cell carcinoma of the ovary arising in a mature cystic teratoma, surgical stage Ic2. In view of the poor prognosis, adjuvant chemotherapy was started.